Stress and Coping Strategies among Thai Medical Students in a Southern Medical School - Norphun, Naruttha; Pitanupong, Jarurin; Jiraphan, Aimorn (Siriraj Medical Journal, 2020)
Objective: To assess stress, and coping strategies and related factors among medical students. Methods: This cross-sectional study surveyed all 1st to 6th year medical students at the Faculty of Medicine, Prince of Songkla University, from March to May, 2019. Three questionnaires were employed: 1) Demographic data 2) The Suanprung stress test 3) The Brief COPE inventory Thai version. Data were analyzed using descriptive statistics, and the results were presented as percentage, frequency, average and standard deviation. Factors associated with coping strategies were analyzed by means of chi-square or kruskal-wallis test. Results: There were 827 respondents from 1,109 medical students, and 74.6% response rate. The majority of medical students were female (60.7%) with moderate and high stress level scores (44.9% and 38.6%, respectively). The medical students commonly used adaptive coping strategies (self-distraction, acceptance, active coping, and positive reframing) rather than maladaptive coping strategies (denial and substance use). According to the association between general demographic characteristics and coping strategies, we found that; gender, GPA, religion and medical illness had significant correlation with adaptive coping strategies. Whereas, high stress levels were significantly associated with maladaptive coping strategies. Conclusion: Most medical students use adaptive coping strategies. Gender, GPA, religion and medical illness had significant correlation with adaptive coping strategies.